Mediation Of Buying Interest On Price Perception And Product Quality Towards Acer Laptop Purchase Decisions - Yuniarti, Puji; Zulkifli, Zulkifli; Wianti, Wiwin; Yulistria, Resti; Haryati, Raden Ati; Irawan, Roy; Karlina, Eulin; Taruna, Helmy Ivan (IJOSMAS, 2022)
This study intends to investigate how consumer interest in buying affects consumer perceptions of product quality and pricing while making decisions to buy Acer laptops. Users of Acer laptops in Jakarta who were sampled for this study by completing an online questionnaire made up the respondents. Purposive sampling was used as the method of data gathering. Software called SmartPLS 3.0 is used to process the collected data. The study's findings show that only price perceptions have an impact on consumers' decisions to buy Acer laptops, and that buying interest is not a significant mediating element that influences both price perception and product quality.